Possibilities of novel technologies application for purposes of tourism of people with special needs - Mirosława Szark-Eckardt; Beata Augustyńska; Emilia Mikołajewska; Dariusz Mikołajewski; Mariusz Zasada (Economic and Environmental Studies (E&ES), 2018)
This article aims at investigating the extent to which the available opportunities are being exploited, including current and potential possibilities of novel technologies application for purposes of tourism of people with special needs. The research methods used were: logical-compartmental analysis and observation. Main results of analysis: Development of the knowledge-based economy, studies in it, and implementation of their results in practice, bring many untapped opportunities, including wider application of e-tourism in meeting requirements and needs of disabled people, elderly people or other groups, which have rarely been taken into consideration as separate groups within economic analyses. Practical implications: There is a need for working out novel business models, including the area of e-tourism for people with special needs, which will take into consideration national requirements and domestic possibilities.
Keywords: I12; I31 : Q26; 330; tourism; recreation; local economy; disabled people; elderly people